Determination of Specific Heat and Thermal Conductivity of "Loco" (Concholepas Concholepas) - Reyes-Salinas, A; Mahn-Osses, A (2013)
The specific heat and the thermal conductivity of "loco" slices, a South American mollusk very similar to abalone, were determined at different temperatures and moisture contents. The specific heat values showed a direct proportional increment with moisture content, and to a lesser extent with temperature. A linear model, in terms of temperature and moisture content, was fitted to the experimental data. A good determination coefficient was obtained (94.4%), and then this model could be used for predicting specific heat of loco and other seafood. Thermal conductivities at different moisture contents determined in this work were compared with those predicted by models reported in literature. Significant deviations were observed, showing that the existing models are not suitable for loco. A new correlation is proposed based on our experimental data, which gives a better fit. © 2011 Springer Science+Business Media, LLC.